PENANAMAN NILAI-NILAI ANTI KORUPSI MELALUI KEGIATAN PEMBELAJARAN OUTING CLASS PENDIDIKAN KEWARGANEGARAAN (STUDI PADA SEKOLAH MENENGAH ATAS MUHAMMADIYAH 1 KARANGANYAR) - Atin Putri Sanyoto; Triana Rejekiningsih; Muhammad Hendri Nuryadi (Jurnal PPKn, 2019)
The objectives of research were (1) to find out the inculcation of anti-corruption values through Civic Education outing class learning activity to the students of SMA Muhammadiyah 1 Karanganyar, (2) to find out the effect of anti-corruption values through Civic Education outing class learning activity on the character of students in SMA Muhammadiyah 1 Karanganyar, and (3) to find out the supporting and inhibiting factors in inculcating anti-corruption values through Civic Education outing class learning activity to the students of SMA Muhammadiyah 1 Karanganyar. The results of research were as follows. (1) The inculcation of anti-corruption values in SMA Muhammadiyah 1 Karanganyar was conducted through a series of Civic Education outing class learning activities: a) Pre-activity include event planning with overall appointment and distribution of students to enable everyone to participate actively; b) Anti-corruption Seminar Socialization; c) Court Simulation of Corruption Crime; d) Anti-corruption declaration, e) Anti-Corruption Poetry Reading Competition; f) Anti-Corruption (Islam) proselytizer (Dai) competition, g) Anti-corruption Wall Magazine Competition; h) Anti-Corruption Band Competition; i) Anti-Corruption Pin Wearing; and j) Honesty Canteen; (2) The effect of inculcation anti-corruption values on Students? Character included: the success in moral knowledge with increasing knowledges of corrupt act and anti-corruption values, on moral feelings with the dislike of acts of corruption, but not in moral action, there is a wish to have anti-corruption attitude but it is not accompanied with habituation so that the anti-corruption character has not been created comprehensively; (3) Supporting and inhibiting  factors in inculcating anti-corruption values were as follows. a) Supporting factors included: teacher?s role modeling by giving example to his students as role model by means of rewarding the disciplined teacher and the teachers? creativity to encourage the creation of idea to hold Civic Education outing class learning activity by inculcating nine anti-corruption integrity value; b) Inhibiting  factors included limited fund source, individual?s corrupt habit, and community environment in which non-transparency and illegal levy are still found.   Full Paper